2021
DOI: 10.3390/microorganisms9051102
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Antifouling Performance of Different Marine Surfaces and Their Effect on the Development and Structure of Cyanobacterial Biofilms

Abstract: Since biofilm formation by microfoulers significantly contributes to the fouling process, it is important to evaluate the performance of marine surfaces to prevent biofilm formation, as well as understand their interactions with microfoulers and how these affect biofilm development and structure. In this study, the long-term performance of five surface materials—glass, perspex, polystyrene, epoxy-coated glass, and a silicone hydrogel coating—in inhibiting biofilm formation by cyanobacteria was evaluated. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Moreover, one of the key issues in the development of new AF surfaces is the necessary screening of candidate surfaces (usually tested in vitro in a first step prior to in situ testing) before scale-up and final performance evaluation. Since it has been shown that hydrodynamics can severely affect biofilm formation [ 87 , 88 , 89 , 90 ] and gene expression by fouling organisms [ 91 , 92 ], it is recommended that these tests be performed in controlled hydrodynamic conditions that mimic the final application scenario [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, one of the key issues in the development of new AF surfaces is the necessary screening of candidate surfaces (usually tested in vitro in a first step prior to in situ testing) before scale-up and final performance evaluation. Since it has been shown that hydrodynamics can severely affect biofilm formation [ 87 , 88 , 89 , 90 ] and gene expression by fouling organisms [ 91 , 92 ], it is recommended that these tests be performed in controlled hydrodynamic conditions that mimic the final application scenario [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…These devices are easy to handle, which allows for studying the adhesion of different microbial strains and consequent biofilm formation in rapid and inexpensive assays, due to their reduced volume [ 69 ]. Depending on the format used, they enable high throughput at an affordable cost and sometimes non-invasive imaging through optical coherence tomography (OCT) [ 70 , 71 ] and confocal laser scanning microscopy (CLSM) [ 72 ]. Particularly for larger well dimensions, it is possible to place coupons at the bottom of the wells so that different surface materials can be tested [ 70 , 73 , 74 ].…”
Section: Biofilm Platformsmentioning
confidence: 99%
“…Depending on the format used, they enable high throughput at an affordable cost and sometimes non-invasive imaging through optical coherence tomography (OCT) [ 70 , 71 ] and confocal laser scanning microscopy (CLSM) [ 72 ]. Particularly for larger well dimensions, it is possible to place coupons at the bottom of the wells so that different surface materials can be tested [ 70 , 73 , 74 ]. The main limitations of microplates are that loosely attached cells may not be measured correctly due to detachment during washing and that biofilms formed in this platform are affected by sedimentation.…”
Section: Biofilm Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cyanobacteria proteomics has dealt with many technical challenges 22 , cyanobacteria molecular biology is a promising field for further advancements 23 , 24 . The fouling surface properties and shear rate are two parameters that have a critical impact on marine biofilms 25 , 26 . In a previous qualitative proteomic study, the proteomic profile of biofilm cells from two cyanobacterial strains developed on glass and perspex, and at different shear forces was analysed 27 .…”
Section: Introductionmentioning
confidence: 99%